Far apart, yet close together: Cooperative learning in online education - Francisca M. Ivone; George M. Jacobs; Willy A. Renandya (Studies in English Language and Education, 2020)
Online education can play a crucial role in increasing access to educational opportunity and in promoting lifelong learning. The Covid-19 pandemic has done even more to raise awareness of the importance of online education. The pandemic has been a Category 5 disruptor of education systems. This article was written to help teachers at all levels of education facilitate cooperation among their students as a key element of online education. While many teachers believe in the benefits of student-student cooperation, and theory and research support this view, many teachers worry that distance learning is already difficult enough without adding the complications of cooperative learning, no matter how beneficial it might be. The article begins by discussing some of the obstacles teachers may encounter as they seek to integrate cooperative learning as part of online education. The main part of the article presents nine lesson plans for language education via cooperative learning in online education settings. While the content of the lessons focuses on language learning, the lessons can be employed in a wide variety of content areas. The article concludes with general suggestions on overcoming the previously mentioned obstacles.